Songs of the spirit from Dufftown. (May 2019) - Noden, Shelagh
Abstract : Following the Scottish Catholic Relief Act of 1793, Scottish Catholics were at last free to break the silence imposed by the harsh penal laws, and attempt to reintroduce singing into their worship. At first opposed by Bishop George Hay, the enthusiasm for liturgical music took hold in the early years of the nineteenth century, but the fledgling choirs were hampered both by a lack of any tradition upon which to draw, and by the absence of suitable resources. To the rescue came the priest-musician, George Gordon, a graduate of the Royal Scots College in Valladolid. After his ordination and return to Scotland he worked tirelessly in forming choirs, training organists and advising on all aspects of church music. His crowning achievement was the production, at his own expense, of a two-volume collection of church music for the use of small choirs, which remained in use well into the twentieth century.